Dykha O.V., Vychavka A.A., Velboi V.P. Wear models of sliding guides with lubrication profiles of variable depth - Диха, О.В.; Вичавка, А.А.; Вельбой, В.П. (Problems of Tribology, 2017)
The calculation of the areas of contact and contact pressure for sliding guides with grease grooves of variable depth are round and triangular profiles with consideration of the kinetics of wear is implemented. The proposed direct solution of contact problems with wear to the flat slide guides with lubrication grooves of variable depth. For the base model of the wear adopted linear dependence on the dimensionless complexes of the contact pressure and sliding speed. The formulas for calcu-lating the wear of the guides of the slide in the path dependence of friction and examples of the calculation of the wear of the guides is received.Keywords: guide rail sliding, lubricating groove, the contact pressure, calculation of wear, round or tri-angular profile